Exploring the Diffusion of Digital Technologies in Higher Education Entrepreneurship: The Impact of the Utilization of AI and TikTok on Student Entrepreneurial Knowledge, Experience, and Business Performance - Hisar Sirait; Hendratmoko; Rizqy Aziz Basuki; Rahmat Aidil Djubair; Gavin Torinno Hardipura; Endri Endri (Administrative Sciences)
This study investigates the impact of digital technology propagation, specifically artificial intelligence (AI) and the TikTok application, on enhancing student entrepreneurs’ entrepreneurial knowledge, business experience, and the performance of their ventures. This research employs a mixed-methods design, combining qualitative and quantitative elements, with the quantitative aspect analyzed through Structural Equation Modeling–Partial Least Squares (SEM–PLS) and the qualitative aspect analyzed through in-depth interviews with student entrepreneurs. The survey included participation from 125 students, with three additional students serving as key informants. Research findings suggest that AI directly enhances entrepreneurial knowledge and business performance, whereas TikTok indirectly influences business success by affecting the acquisition of entrepreneurial learning. The utilization of AI has a substantial direct impact on entrepreneurial expertise and business performance. In contrast, the utilization of TikTok has a moderate influence on entrepreneurial knowledge, which in turn mediates its effect on entrepreneurial success. Offer practical implications for higher education institutions to integrate AI-driven analytics and social media marketing strategies into entrepreneurship curricula. Future research should investigate the regulatory framework, long-term implications, and the inclusion of other digital platforms to refine the digital transformation of entrepreneurship education further.